2021
DOI: 10.1111/jace.17654
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave generation by mode conversion in picosecond ultrasonics: Impact of grain orientation and material properties

Abstract: Picosecond ultrasonics has seen wide application in the investigation of interfaces in semiconductors and 3D imaging in biological systems. Shear ultrasonic waves are important for elastic constant and grain orientation measurement in ceramic materials. In this study, we investigate the impact of grain orientation and material's elastic properties on the generation efficiency of shear waves by mode conversion at a transducer thin film/substrate interface. The solution of acoustic wave equations suggests that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…Generation efficiency of transverse acoustic waves has been recently studied in Ref. [68] . By considering multiple crystallite orientations, an estimate of the Brillouin frequency (BF) range can be obtained for each acoustic mode ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Generation efficiency of transverse acoustic waves has been recently studied in Ref. [68] . By considering multiple crystallite orientations, an estimate of the Brillouin frequency (BF) range can be obtained for each acoustic mode ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it is worthy of attention that Eq. (7) requires further generalization if the interested orientation along the z -axis is not symmetric [51] . Additionally, is the phase velocity of the longitudinal mode in the MS-substrate along the z -axis, which is given by where represents the element in the third row and third column of the silicon stiffness matrix with respect to the global coordinate system (G-CSYS), as shown in Fig.…”
Section: Oa-ubw In Ms: Generation and Propagationmentioning
confidence: 99%
“…This has motivated recent endeavors to explore and make use of the shear strains induced by OA-UBW in crystalline materials, with paradigms including nondestructive evaluation of microscopic elastic properties of monocrystalline silicon [50] , calibration of the crystalline grain orientation of transparent ceria ceramic substrates [51] , and sound-velocity based work function analysis for semiconducting two-dimensional electronic materials [52] . Success of these applications has further inspired the use of shear strains for characterization of MS. Gusev [53] theoretically demonstrated that the plane shear waves can be generated in a submicron layer made of an elastically isotropic materials, by means of a laser-induced transient grating, to quantify the shear rigidity and shear viscosity of the layer.…”
Section: Introductionmentioning
confidence: 99%